Laser modification of structure and optical properties of N-doped graphene oxide - Seliverstova, E.; Ibrayev, N.; Menshova, E.; Alikhaidarova, E. (Materials research express, 2021)
The effect of laser ablation of N-doped graphene oxide (NGO) sheets on its optical properties has been studied. It was shown that the average lateral size of NGO sheets was decreased from 644.4 +/- 143.8 to 114.4 +/- 59.8 nm after 60 min of ablation. The data of FTIR spectroscopy have shown that after ablation the intensity of the vibrations bands of N-containing groups increases. The optical density of NGO dispersions and the intensity of their emission are depended on the ablation time. The highest fluorescence intensity was recorded upon excitation at a wavelength of 350 nm. For all NGO samples after laser irradiation a noticeable increase in the fluorescence intensity was registered. The enhancement factor was equal to similar to 11.0 and 8.5 times for 30 and 60 min, respectively. The lifetime of NGO fluorescence after ablation was increased from 1.73 ns to 3.63 ns. After ablation, the samples under study exhibit long-term luminescence with a maximum at about 450 nm. The data obtained open up possibilities to control the optical properties of N-doped graphene oxide and nanodots based on it.
Keywords: N-doped graphene oxide; laser ablation; dots; luminescence